Responsiveness of the Investment Office and One-Stop Integrated Services of East Luwu Regency in the Service of Trade Business Licenses - Joyakin Damanik; Sangkala Sangkala; Agus Santosa (Jurnal Indonesia Sosial Teknologi, 2024)
The responsiveness of the Trading Business License (SIUP) licensing service provider is very important to create a pleasant and excellent licensing service system. Simplification of the number and types of licensing and non-licensing has been carried out, from 142 types to 34 types. Through the online system, it is easier for applicants to register and monitor the flow of permits and can speed up the licensing process time, one day service. The Department of Investment and One Stop Integrated Services (DPMPTSP) has made various efforts to increase the responsiveness of SIUP services, but based on preliminary research conducted by researchers, it shows that the level of responsiveness of the East Luwu Regency DPMPTSP is still not optimal, being in the "sufficient" category. This research aims to analyze the level of responsiveness and factors that hinder the responsiveness of SIUP services in DPMPTSP East Luwu Regency. The research used a descriptive quantitative approach, with a questionnaire instrument to collect data from 100 respondents from a population of 1,342 people. The sample taker used a simple random sampling technique. Data processing using SPSS version 22, was then analyzed using Weight Means Score (WMS). The level of responsiveness of DPMDPTSP East Luwu Regency in SIUP services, an average of 3.41 (fair) indicates that responsiveness is not optimal, especially in terms of speed of service, timeliness of service, and response to every applicant's complaint as stated by Zeithaml et al (1990) that Daya Responsiveness is the willingness and readiness to help provide immediate service, such as punctuality of service, responding to every applicant, service quickly, precisely and carefully.